The use of acoustic rhinometry as a postoperative evaluation method in children with chronic hypertrophic rhinitis - Fuculița, Daniel (The Ukrainian Scientific Medical Youth Journal, 2023)
acoustic rhinometry has opened new perspectives in the objective estimation of nasal physiology. With the help of this method, it is easy to determine the geometry of the nasal fossae, using minimal resources. The method offers an objective control of the surgery of the cartilages and bones of the nasal pyramid. That method represents an objective method of measuring nasal permeability, which in recent years is increasingly used in pediatric patients. In this study, we aim to evaluate nasal patency in children with chronic hypertrophic rhinitis. Study of nasal permeability using acoustic rhinometry in children with chronic hypertrophic rhinitis in order to evaluate the effectiveness of diode laser surgical treatment for hypertrophy of the inferior nasal turbinate. The study was conducted on 50 children with chronic hypertrophic rhinitis. The comparison group was represented by the control group, which includes 50 children without nose and paranasal sinus pathology. These children were selected from the number of patients hospitalized in the clinic with other forms of pathology. In patients from the study groups, nasal patency was evaluated at certain postoperative time intervals, in order to determine the efficiency of the applied surgical technique. There is a dynamic increase in nasal cavity volumes and ASTmin postoperatively in patients from the study group. Compared to the control group, the differences are insignificant, which indicates that the surgical treatment had an effect. Acoustic rhinometry is an objective method of evaluating the geometry of the nasal cavities, with a special role in the postoperative monitoring of patients with chronic hypertrophic rhinitis